Obesity phenotypes are, in part, associated with physical activity in diabetic hemodialysis patients - de Oliveira Matos, Beatriz; da Costa Rosa, Clara Suemi [UNESP]; Ribeiro, Heitor Siqueira; Marcos, Natasha Maggi; Losilla, Milene Peron Rodrigues; Monteiro, Henrique Luiz [UNESP]; Gimenes, Camila (Springer Nature, 2021)
Purpose: To investigate the prevalence of obesity phenotypes and their association with physical activity levels among diabetic hemodialysis patients. Methods: This is a cross-sectional study with 84 diabetic hemodialysis patients (63.5 ± 9.4 years, 54.8% of men). Obesity was diagnosed as high body fat (≥ 40% for male and ≥ 30% for female). Sarcopenic obesity was considered if low skeletal muscle mass (< 20.0 kg for males and < 15.0 kg for females) and obesity were combined. Dynapenic obesity was defined in the presence of low handgrip strength (< 27 kg for males and < 16 kg for females) and obesity. Muscle failure obesity was confirmed in the concomitant presence of obesity, sarcopenia, and dynapenia. Physical activity level was assessed by the Baecke questionnaire and patients were classified as low physical activity according to the first tertile for each of and total domains. Results: Fifty-four patients (64%) presented obesity. From these, 5 (6%), 19 (23%) and 8 (10%) were classified as sarcopenic obese, dynapenic obese, and muscle failure obese, respectively, and 22 (26%) were only obese. Patients with sarcopenic obesity and muscle failure obesity had lower leisure and locomotion physical activity scores than non-obese, whereas the total domain score did not differ across the groups. Muscle failure obesity was independently associated with low leisure physical activity (OR 10.8, 95% CI 1.3–88.1). Only sarcopenic obesity was independently associated with the locomotion and total physical activity domains (OR 15.4, 95% CI 1.4–90.2 and OR 17.0, 95% CI 1.5–95.4, respectively). Conclusion: Our study found a lower prevalence of sarcopenic obesity compared to dynapenic obesity and muscle failure obesity among diabetic hemodialysis patients. Moreover, sarcopenic obesity and muscle failure obesity, but not dynapenic obesity, were associated with low physical activity levels.
Keywords: Chronic kidney disease; Dynapenia; Obesity; Physical activity; Sarcopenia